POLA ASUH IBU SEBAGAI ORANG TUA TUNGGAL DALAM MEMBENTUK KEMANDIRIAN ANAK DI DESA BISSOLORO KECAMATAN BUNGAYA KABUPATEN GOWA - Musfira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2020)
Abstract: Parenting of Mothers as Single Parents In Shaping Children's Independence In Bissoloro Village, Bungaya District, Gowa Regency. This study aims to find out parenting mothers as single parents in shaping children's independence in Bissoloro Village, Bungaya District, Gowa Regency for Education Implementers. Penelitian i merupakan research approaches descriptively qualitatively. Populasi penelitian ini adalah selyouruh the subjects in this study were single parents and children. Where the number of single parents is 2 people. The data collection techniques used in this study are interviews, observations, documentation. Hasil analisi s theconclusion that from both mothers of single parents who took care of their children patiently and never yelled at their children. Mrs. ARW, in addition to guiding the child patiently, she also instilled good attitudes in her child. Providing encouragement is also learning how a boy should fulfill his responsibilities at home and also increase the child's independence.